2000
DOI: 10.1016/s0022-5347(05)66935-2
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Receptor Gene Amplification at Primary Progression Predicts Response to Combined Androgen Blockade as Second Line Therapy for Advanced Prostate Cancer

Abstract: Androgen receptor gene amplification detected in tumors progressing during androgen deprivation monotherapy is associated with favorable treatment response to second line combined androgen blockade. This finding suggests that at least some androgen receptor amplified tumors retain a high degree of dependency on residual androgens remaining in serum after monotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(44 citation statements)
references
References 18 publications
0
44
0
Order By: Relevance
“…23 AR amplification may also sensitize AR to activation by low levels of precursor adrenal androgens. 24 Moreover, in tumor cells overexpressing AR coactivators SRC-1 and TIF2, higher the AR activities were measured after treatment with precursor adrenal androgens. 25 Such data suggest that precursor adrenal androgens participate in the transition to androgen independency via mechanisms that relate to AR hypersensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…23 AR amplification may also sensitize AR to activation by low levels of precursor adrenal androgens. 24 Moreover, in tumor cells overexpressing AR coactivators SRC-1 and TIF2, higher the AR activities were measured after treatment with precursor adrenal androgens. 25 Such data suggest that precursor adrenal androgens participate in the transition to androgen independency via mechanisms that relate to AR hypersensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…It was seen that amplification positively correlated with increase in PSA in one study 20 but not in the others. 18,19,26 Furthermore, Ford et al 18 showed that there was no difference in the survival of the patients with or without amplification. In addition, studies show that amplification is not a common feature of all HR tumors.…”
Section: Amplification Of the Armentioning
confidence: 99%
“…However, almost all of the patients whose tumors overexpressed ARs underwent androgen-deprivation monotherapy without the administration of anti-androgens. Another report by Palmberg et al (2000) evaluated whether AR gene amplification at the primary progression of prostate cancer is associated with a response to a second-line maximum androgen blockade (MAB). Patients with AR gene amplification also had a decrease in serum prostate-specific antigen (PSA) more often after MAB than those with no amplification (P = 0.079).…”
Section: Loss Of Hormone Sensitivity In Prostate Cancermentioning
confidence: 99%